2021
DOI: 10.1016/s1473-3099(21)00262-0
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 B.1.1.7 and B.1.351 spike variants bind human ACE2 with increased affinity

Abstract: SARS-CoV-2 B.1.1.7 and B.1.351 spike variants bind human ACE2 with increased affinity Genomic surveillance efforts have uncovered SARS-CoV-2 variants with mutations in the viral spike glycoprotein, which binds the human angiotensin-converting enzyme 2 (ACE2) receptor to facilitate viral entry. 1 Such variants represent a public health challenge during the COVID-19 pandemic because they increase viral transmission and disease severity. 2 The B.1.351 variant, first identified in South Africa, has three notable m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 5 publications
12
128
1
Order By: Relevance
“…Of note, these Spike proteins also differ in their N-terminal sequences (NTD), which is thought to also contribute to the Spike RBD-ACE2 interaction. Some of these mutations have been associated with increased virus transmissibility [42][43][44]. [46][47][48][49][50], the current study revealed rank-ordered neutralization capability against a series of additional Spike variants with distinct mutations in RBD.…”
Section: Cross-reactivity Of Vaccine-induced Nabmentioning
confidence: 76%
“…Of note, these Spike proteins also differ in their N-terminal sequences (NTD), which is thought to also contribute to the Spike RBD-ACE2 interaction. Some of these mutations have been associated with increased virus transmissibility [42][43][44]. [46][47][48][49][50], the current study revealed rank-ordered neutralization capability against a series of additional Spike variants with distinct mutations in RBD.…”
Section: Cross-reactivity Of Vaccine-induced Nabmentioning
confidence: 76%
“…The copyright holder for this preprint this version posted July 6, 2021. ; https://doi.org/10.1101/2021.07.01.21259404 doi: medRxiv preprint (Martin et al, 2021). Likewise, both VOCs Alpha and Gamma share the mutation N501Y, also implicated in immune escape and enhancement of the affinity between the RBD and human angiotensin converting enzyme 2 (ACE2), the cellular receptor used by SARS-CoV-2 for cell entry (Lan et al, 2020;Ramanathan et al, 2021). These functional effects, joint to the fast observed rise in frequency and number of cases across diverse epidemiological settings (Barbosa et al, 2021;Franceschi et al, 2021;Moreira et al, 2021a;Naveca et al, 2021) -including the one herein reported -provide evidence that the VOC Gamma has a fitness advantage over previously circulating lineages.…”
Section: -Discussionmentioning
confidence: 99%
“…In this work, we report that the SARS-CoV-2 gained the novel S1-NTD in its genome. Most of the studies focused on the rapid spread of the SARS-CoV-2 due to its S1-RBD diversity to binds with the human ACE2 receptor and the presence of a specific furin cleavage site (FCS) 4,[29][30][31][32][33][34][35] . However, the furin cleavage site is not only present in SARS-CoV-2, but also present in MERS-CoV, HKU1, and HCoV-OC43 4,32,34,36 , and the SARS-CoV-2 without FCS also can infect target cells efficiently in the presence of trypsin or human airway trypsin-like protease (HAT) 37 .…”
Section: Discussionmentioning
confidence: 99%